Air quality and radiative impacts of downward-propagating sudden stratospheric warmings (SSWs) - R. S. Williams; R. S. Williams; M. I. Hegglin; M. I. Hegglin; P. Jöckel; H. Garny; K. P. Shine (Atmospheric Chemistry and Physics, 2024)
Sudden stratospheric warmings (SSWs) are abrupt disturbances to the Northern Hemisphere wintertime stratospheric polar vortex that can lead to pronounced regional changes in surface temperature and precipitation. SSWs also strongly impact the distribution of chemical constituents within the stratosphere, but the implications of these changes for stratosphere–troposphere exchange (STE) and radiative effects in the upper troposphere–lower stratosphere (UTLS) have not been extensively studied. Here we show, based on a specified-dynamics simulations from the European Centre for Medium-Range Weather Forecasts – Hamburg (ECHAM)/Modular Earth Submodel System (MESSy) Atmospheric Chemistry (EMAC) chemistry–climate model, that SSWs lead to a pronounced increase in high-latitude ozone just above the tropopause (>25 % relative to climatology), persisting for up to 50 d for the ∼50 % of events classified as downward propagating following Hitchcock et al. (2013). This anomalous feature in lowermost-stratospheric ozone is verified from ozone sonde soundings and using the Copernicus Atmospheric Monitoring Service (CAMS) atmospheric composition reanalysis product. A significant dipole anomaly (>± 25 %) in water vapour also persists in this region for up to 75 d, with a drying signal above a region of moistening, also evident within the CAMS reanalysis. An enhancement in STE leads to a significant 5 %–10 % increase in near-surface ozone of stratospheric origin over the Arctic, with a typical time lag between 20 and 80 d. The signal also propagates to mid-latitudes, leading to significant enhancements in UTLS ozone and also, with weakened strength, in free tropospheric and near-surface ozone up to 90 d after the event. In quantifying the potential significance for surface air quality breaches above ozone regulatory standards, a risk enhancement of up to a factor of 2 to 3 is calculated following such events. The chemical composition perturbations in the Arctic UTLS result in radiatively driven Arctic stratospheric temperature changes of around 2 K. An idealized sensitivity evaluation highlights the changing radiative importance of both ozone and water vapour perturbations with seasonality. Our results highlight that, whilst any background increase in near-surface ozone due to SSW-related stratosphere-to-troposphere (STT) transport is likely to be small, this could be of greater importance locally (e.g. mountainous regions more susceptible to elevated ozone levels). Accurate representation of UTLS composition (namely ozone and water vapour), through its effects on local temperatures, may also help improve numerical weather prediction forecasts on sub-seasonal to seasonal timescales.